2012
DOI: 10.1136/sextrans-2011-050219
|View full text |Cite
|
Sign up to set email alerts
|

Systematic selection of screening participants by risk score in a chlamydia screening programme is feasible and effective

Abstract: Objectives Systematic screening for Chlamydia trachomatis by individual invitation can be optimised by filtering participants on risk profile, excluding people at no or low risk. The authors investigated this technique in a large-scale chlamydia screening programme in the Netherlands in one rural region where relatively low prevalence was expected (<2%). Methods Invitees were alerted by personal letter to log in to http://www.chlamydiatest.nl and fill in an 8-item questionnaire. Only invitees with sufficient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…This may enable clinicians to effectively determine whether triaging those with low-risk scores to receive "express" services (e.g., providing self-collected specimens) or referring others to more comprehensive services (e.g., complete physical examinations). 8 This process may help decrease wait times, improve clinical workflow, and reduce unnecessary clinician face time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may enable clinicians to effectively determine whether triaging those with low-risk scores to receive "express" services (e.g., providing self-collected specimens) or referring others to more comprehensive services (e.g., complete physical examinations). 8 This process may help decrease wait times, improve clinical workflow, and reduce unnecessary clinician face time.…”
Section: Discussionmentioning
confidence: 99%
“…7 To maximize case finding in asymptomatic visits, selective screening (based on risk assessment and entails the screening of individuals who meet prespecified criteria) may be a prudent approach because it minimizes the costs associated with testing low-risk individuals. 8 The current body of knowledge indicates that risk prediction rules that capture a continuous risk spectrum are excellent tools for targeted screening. 9 A recent review critically appraising prediction rules used for sexual health service provision found that these have been explored in a variety of contexts including emergency departments, population-based settings and STI clinics.…”
mentioning
confidence: 99%
“…The score charts may be useful to select high-risk individuals as part of systematic screening programmes in urban areas, similar to the selection of individuals at high risk in less urban regions 10. Furthermore, the score charts may be used in guiding STI clinicians and GPs whom to offer opportunistic Ct testing—more selectively than using age group alone.…”
Section: Discussionmentioning
confidence: 99%
“…A screening programme trialled in the Netherlands used information on young people's SEC to exclude those with low or no risk of chlamydia. The researchers concluded that this selective approach achieved higher positivity in their population compared with screening all young people 10. However, a more recent systematic review to examine socioeconomic associations with chlamydia concluded that the relationship is unclear and called for more research to build a ‘deeper understanding’ of chlamydia's relationship with social factors 11.…”
Section: Introductionmentioning
confidence: 99%